Inequalities and Extremal Problems in Probability and Statistics - Pinelis,I; Peña,VHDL; Ibragimov,R; Shevtsova,I; Oskowski,AO (Academic Press, 2017)
The book enables the reader to grasp the importance of inequalities and how they relate to probability and statistics.